Development of a GIS Based Water Management Tool for a Large Scale Rice Irrigation Scheme - M. K., Rowshon; C. Y., Kwok; T. S., Lee (Universiti Putra Malaysia Press, 2002)
A GIS based model was developed to integrate the vast amounts of spatially distributed information from the Kerian Irrigation Scheme comprising eight compartments which are further subdivided into 28 blocks. The model consists of three modules. The "Scheduling" program computes irrigation deliveries based on spatial and temporal demand of the paddy field by each compartment, block or secondary canal. The "Monitoring" program gives information by compartment and by block on the uniformity of water distribution and the shortfall or excess. Relative Water Supply (RWS), Water Use Efficiency (WUE), Cumulative Relative Water Supply (CRWS), and Water Productivity Index (WPI) were computed by the "Evaluation" module. The post-season analysis uses weekly information on hydro-climatic parameters, irrigation delivery and irrigation indices by block within each compartment. On a weekly basis, RWS and WUE were found to range from 1.01 to 2.24 and 45% to 99% respectively in the main season and 1.01 to 1.87 and 53.57% to 96.15% respectively in the off season. The average values of RWS and WUE were found to be 1.53 and 68.15% in the main season and 1.33 and 78.47% in the off season respectively. The average values of WPI were also found to be 0.13 and 0.22 kg/m3 in the main season and off seasons respectively. Color-eoded thematic maps were produced for the monitoring of Seasonal Yields and Cropping Intensity (CI) by block and compartment of the scheme. The results are displayed allowing the manager to view maps, tables and graphs in a comprehensible form to ease decision making as the season progresses. This study would be useful to improve the irrigation system management based on feedback of field information.